Calcium-sensitive regulation of actin-myosin interactions in baby hamster kidney (BHK-21) cells. - Yerna, M J (1979)
A fraction has been obtained from baby hamster kidney (BHK-21) cells that will stimulate the actin-moderated ATPase (ATP phosphohydrolase, EC 3.6.1.3) activity of both BHK-21 myosin and gizzard smooth muscle myosin. This activation is associated with the specific phosphorylation of the myosin 20,000-dalton light chain. The BHK-21 myosin light chain kinase preparation contains a major protein of approximately 105,000 molecular weight as determined by sodium dodecyl sulfate gel electrophoresis. Both the actin activation and phosphorylation events require the presence of Ca2+ and the so-called modulator or calcium-dependent regulator protein that has been isolated from smooth muscle, brain, and other tissues. On the basis of these results we propose that this kinase system constitutes a Ca2+-dependent regulatory mechanism for myosin-actin interactions in nonmuscle mammalian cells.